2015
DOI: 10.5455/medarh.2015.69.169-172
|View full text |Cite
|
Sign up to set email alerts
|

The Infraorbital Artery in Fetuses: Clinical Relevance in Perforator Flap Surgery

Abstract: Introduction:The reconstruction of soft tissue detects in mid facial region are highly demanding. Most challenging region are nasal alla. For full thickness nasal alla defects most authors use nasolabial flap based on facial/angular arcade, but for recidivans tumors the infraorbital perforator flap is a good solution.Aim:The aim of our research was to analyze the number and the course of the infraorbital artery terminal branches.Material and methods:Material was 60 fetal hemifacial specimens of different gesta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…The only existing anatomical study and classification regarding the IOA was established by Kovacevic et al by means of microdissection on fetuses. Their findings were similar to ours …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The only existing anatomical study and classification regarding the IOA was established by Kovacevic et al by means of microdissection on fetuses. Their findings were similar to ours …”
Section: Discussionsupporting
confidence: 92%
“…Several authors have already suggested the use of perforator and axial local cutaneous flaps based on the IOA for soft tissue reconstruction for full‐thickness defects of the nose, but none of the proposed techniques described a mucosal perforator flap . Recently, mucosal perforator flaps arising from the facial artery have been reported and are relevant in mucosal cheek reconstruction …”
Section: Discussionmentioning
confidence: 99%